2017
DOI: 10.1016/j.celrep.2017.10.116
|View full text |Cite
|
Sign up to set email alerts
|

Disparate Postsynaptic Induction Mechanisms Ultimately Converge to Drive the Retrograde Enhancement of Presynaptic Efficacy

Abstract: SUMMARY Retrograde signaling systems are fundamental modes of communication that synapses utilize to dynamically and adaptively modulate activity. However, the inductive mechanisms that gate retrograde communication in the postsynaptic compartment remain enigmatic. We have investigated retrograde signaling at the Drosophila neuromuscular junction, where three seemingly disparate perturbations to the postsynaptic cell trigger a similar enhancement in presynaptic neurotransmitter release. We show that the same p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
117
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(135 citation statements)
references
References 29 publications
16
117
2
Order By: Relevance
“…Recently, it was found that postsynaptic glutamate receptor inhibition and postsynaptic mTOR overexpression enhance release through similar presynaptic mechanisms (Figure 3a; Goel et al, 2017). However, while postsynaptic glutamate receptor impairment resulted in decreased pCaMKII levels, this was not observed after postsynaptic mTOR overexpression (Goel et al, 2017). This indicates that postsynaptic glutamate receptor impairment and mTOR signaling likely control presynaptic release through different pathways.…”
Section: Postsynaptic Mechanismsmentioning
confidence: 95%
See 3 more Smart Citations
“…Recently, it was found that postsynaptic glutamate receptor inhibition and postsynaptic mTOR overexpression enhance release through similar presynaptic mechanisms (Figure 3a; Goel et al, 2017). However, while postsynaptic glutamate receptor impairment resulted in decreased pCaMKII levels, this was not observed after postsynaptic mTOR overexpression (Goel et al, 2017). This indicates that postsynaptic glutamate receptor impairment and mTOR signaling likely control presynaptic release through different pathways.…”
Section: Postsynaptic Mechanismsmentioning
confidence: 95%
“…Retrograde PHP signaling involves multiplexin/ endostatin (Wang et al, 2014) and Sema-2B/Plexin B (Orr et al, 2017). PHP requires postsynaptic mTOR signaling (Goel et al, 2017;Penney et al, 2012), class II PI3 kinase function (Hauswirth et al, 2018), and reduced pCaMKII levels (Goel et al, 2017;Li, Goel, Chen, et al, 2018;Newman et al, 2017). Note that the cartoon only summarizes recent genes implicated in PHP.…”
Section: Physiology and Genesmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies demonstrated that PhTx application results in a rapid increase in the quantity of presynaptic active zone protein Brp, accompanied by an elaboration of the presynaptic cytomatrix structure (Goel et al, 2017;Weyhersmuller et al, 2011). We visualized and quantified the Brp puncta before and after PhTx exposure by confocal microscopy (see Materials and Methods).…”
Section: Neto-α Enables the Fast Recruitment Of The Active Zone Protementioning
confidence: 99%